2013
DOI: 10.1371/journal.pone.0058889
|View full text |Cite
|
Sign up to set email alerts
|

Insect Odorant Response Sensitivity Is Tuned by Metabotropically Autoregulated Olfactory Receptors

Abstract: Insects possess one of the most exquisitely sensitive olfactory systems in the animal kingdom, consisting of three different types of chemosensory receptors: ionotropic glutamate-like receptors (IRs), gustatory receptors (GRs) and odorant receptors (ORs). Both insect ORs and IRs are ligand-gated ion channels, but ORs possess a unique configuration composed of an odorant-specific protein OrX and a ubiquitous coreceptor (Orco). In addition, these two ionotropic receptors confer different tuning properties for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(131 citation statements)
references
References 40 publications
(62 reference statements)
4
123
0
Order By: Relevance
“…This may reflect the inability of the drug to inhibit ACs completely. Similarly, SQ22536 did not suppress OSN activity at high stimulus concentrations (Getahun et al, 2013). As Or22a…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This may reflect the inability of the drug to inhibit ACs completely. Similarly, SQ22536 did not suppress OSN activity at high stimulus concentrations (Getahun et al, 2013). As Or22a…”
Section: Resultsmentioning
confidence: 90%
“…sensitivity, are regulated by multiple intracellular signaling cascades (Nakagawa and Vosshall, 2009;Wicher, 2015). The second messenger 3′,5′-cyclic adenosine monophosphate (cAMP) is an activating ligand for Orco channels (Wicher et al, 2008;Stengl, 2010;Stengl and Funk, 2013) and has been shown to enhance the activity of olfactory sensory neurons (OSNs) that express ORs (Olsson et al, 2011;Getahun et al, 2013). Insect OSNs possess the cellular machinery required to produce cAMP (Iourgenko and Levin, 2000;Boto et al, 2010) and disruption of this signaling cascade has been reported to affect the functional properties of OSNs (Martín et al, 2001;Gomez-Diaz et al, 2004;Deng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the molecular basis for this sensitivity. Studies have shown that the OrX-Orco complex is subject to metabotropic signalling (Stengl, 1993(Stengl, , 2010Kain et al, 2008;Wicher et al, 2008;Deng et al, 2011;Sargsyan et al, 2011;Getahun et al, 2013;Ignatious Raja et al, 2014;Carraher et al, 2015) and also that OrX-Orco activation enhances secondary messenger production (Wicher, et al, 2008;Miazzi et al, 2016). Neither OrX nor Orco has any obvious homology to known cyclic nucleotide binding domains, and it is not clear how these two proteins interact.…”
Section: Introductionmentioning
confidence: 99%
“…This finding could be explained by different hypotheses. It could be hypothesized that MsexOrs and MsexOrco need to be phosphorylated before they can be gated by BAL as an ionotropic odor receptor-ion channel complex, as suggested previously in D. melanogaster (Sargsyan et al, 2011;Getahun et al, 2013). Alternatively, it could be hypothesized that MsexOrs couple to G αq proteins, requiring activation of PLC for pheromone transduction, as suggested by previous findings in moths and cockroaches (Breer et al, 1990;Boekhoff et al, 1993Boekhoff et al, , 1994; for a review, see Stengl, 2010).…”
Section: Plc-and Pkc-dependent Regulation Of Bal Responses In Heterolmentioning
confidence: 78%
“…Next, a possible dependence of the BAL response on PLC or PKC activity was examined, as reported previously for hawkmoth pheromone transduction (Stengl, 1993(Stengl, , 1994(Stengl, , 2010Dolzer et al, 2008) and for fruitfly Orco (Sargsyan et al, 2011;Getahun et al, 2013). Thus, Ca 2+ imaging experiments were performed in HEK293 cells expressing MsexOrco and MsexOr1.…”
Section: Plc-and Pkc-dependent Regulation Of Bal Responses In Heterolmentioning
confidence: 99%